The Effect of Digital Flashcards on Vocabulary Mastery of the 7th Grade Students at SMPN 2 Cibitung - Hudayani, Ria Dewi; Muhammad, Aris Setiawan; Mutiara, Dewi; Nurlela, Neng Siti (JEdu: Journal of English Education, 2025)
Vocabulary is the important thing to learn in English, but there are still many people who find it difficult to master vocabulary because of the lack of media to master it. This research was designed with the aim of finding out the effect of digital flash cards on vocabulary mastery. The design used in this research is quantitative research using pre-experimental methods. The sample in this research was 29 class 7B students at SMPN 2 Cibitung. This research was carried out by conducting a pretest, then continued with treatment for two meetings while observing, then a posttest was held after the treatment. Data in this study were collected using vocabulary test instruments at pretest and posttest, as well as observations made during the treatment. The results of this research show that students' vocabulary mastery increased after carrying out treatment using digital flash card media. This can be seen from the average score which increased from 31,28 to 61,38. Data from the results of the paired sample t-test in the SPSS application shows a significance of <0,001, which is smaller than 0,05. Then, from the observation results, it was found that digital flash cards had a positive impact on students' vocabulary mastery. The data findings from this research indicate that digital flash cards have the effect of increasing vocabulary mastery.